Series solutions of PT-symmetric Schrödinger equations. (7th February 2018) - Bender, Carl M; Ford, C; Hassanpour, Nima; Xia, B
Abstract: A simple and accurate numerical technique for finding eigenvalues, node structure, and expectation values of   -symmetric potentials is devised. The approach involves expanding the solution to the Schrödinger equation in series involving powers of both the coordinate and the energy. The technique is designed to allow one to impose boundary conditions in   -symmetric pairs of Stokes sectors. The method is illustrated by using many examples of   -symmetric potentials in both the unbroken- and broken-   -symmetric regions.